Chapter 4 Origins of Ageism at the Individual Level (2018)
This chapter presents a model that explains the origins of ageism at the individual level among different age groups. The model is based on three theories. Terror management theory provides an explanation for the roots and motives of ageism towards old age groups among young and middle-aged groups as well as among the young-old age group. Stereotype embodiment theory provides a complementary explanation for self-ageism among the young-old and old-old age groups. Finally, social identity theory focuses on the diverse expressions of ageism among different age groups. The model highlights a unique feature of ageism, which, in contrast with other types of prejudice and discrimination, is not directed towards distinct out-groups, but rather towards our future selves by symbolizing a fear of death and its accompanying deterioration. In order to cope with this fear, different age groups differentiate themselves from the old age group by adopting diverse strategies including younger age identities, a distinction between the third and the fourth age, as well as theories like successful and active ageing. Because of the gradual reduction of personal and social resources people often encounter in the later stages of life, we suggest some long-term strategies that recognize decline as a valid dimension of ageing and personhood and emphasize alternative resources.